The Effect of Concentration and Type of Immersion Media (Water, Alcohol, Salt, and Vinegar Acid) on Decreasing Oxalate Levels in Porang - Bambang Sugiarto; Adhi Setyawan; Octavia Nurmalitasari; RR Endang Sulistyowati (Eksergi, 2023)
Porang tubers (Amorphophallus oncophyllus) contain very high levels of glucomannan and have many benefits in various fields of health, pharmaceuticals, industry, and food. Apart from having great benefits, porang tubers contain calcium oxalate which can cause itching if consumed directly, irritation, and kidney stones. This study aimed to determine the decrease in oxalate levels in porang tubers using various concentrations and types of immersion media in porang. The types of immersion media are water, salt, alcohol, and vinegar. Water immersion was carried out at 30°C, 40°C, 50°C, 60°C, and 70°C. Immersion with salt was carried out at concentrations of 6%, 8%, 10%, 12%, and 14%. Immersion with alcohol was carried out at concentrations of 20%, 30%, 40%, 50%, and 60%. The vinegar immersion was carried out at concentrations of 10%, 15%, 20%, 25%, and 30%. Oxalate levels were analyzed by the permanganate titration method. The results of immersion porang with dice and long slices in this study showed that water with a temperature of 50°C in the 5th immersion, alcohol with a concentration of 60% in the 5th immersion, salt solution with a concentration of 14% in the 5th immersion, and acetic acid with a concentration of 30% in the 5th immersion is the optimal result.